La mère, la directrice, la pédagogue et la lectrice : de l’utilisation du sexe comme variable pédagogique chez Pauline Kergomard - Bérengère Kolly (Recherches en Éducation)
L’éducation maternelle dans l’école (The maternal education at school) appears as a new educationalist proposition which intends, by taking its new principles from family context, maternal gestures and home habits to think the education during early childhood. By this way, Pauline Kergomard does aknowledge the necessary circulation between family and school, and differentiates real from philosophical model: her new model of school is thus both in distance with real mother and anchored in “motherly genius”. This distortion between real and fiction does reveal a particularity in the use of the female sex as an educational variable. The female sex of the mother, the teacher, the educationalist and her readers, understood as a historical and not biological variable, does thus become a lever of innovation and creation in educational conceptions and practices.